2022
DOI: 10.3390/ijerph20010472
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 Pandemic on Hospitalization and Interventional Procedures for Cardiovascular Diseases during the First Wave in Italy

Abstract: Coronavirus disease 2019 (COVID-19) has been responsible for an epidemic of devastating proportion, and it has represented a challenge for worldwide healthcare systems with the need of resources reallocation in order to face epidemic spread. Italy was one of the hardest hit countries by COVID-19, and the Italian government adopted strict rules to contain the spread of the COVID-19 pandemic, such as national lockdown and home quarantine; moreover, the Italian healthcare system had to rapidly re-organize the dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
(73 reference statements)
0
2
0
Order By: Relevance
“…While most previous studies compared the COVID-19 period to a prior short period close to the outbreak [6], this study described the incidence of cardiovascular diagnoses and procedures as part of a trend throughout a whole decade. The previous studies that compared the COVID-19 period with a long pre-pandemic period have been mostly limited to a single outcome [34] or a small sample size [17,34] or were based on information that was documented during hospitalizations without considering community clinic records [8,16]. Looking at a whole decade, this study enables health professionals to estimate the consequences of the pandemic on cardiovascular outcomes more accurately and, to a large extent, to rule out the influence of secular trends or random changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While most previous studies compared the COVID-19 period to a prior short period close to the outbreak [6], this study described the incidence of cardiovascular diagnoses and procedures as part of a trend throughout a whole decade. The previous studies that compared the COVID-19 period with a long pre-pandemic period have been mostly limited to a single outcome [34] or a small sample size [17,34] or were based on information that was documented during hospitalizations without considering community clinic records [8,16]. Looking at a whole decade, this study enables health professionals to estimate the consequences of the pandemic on cardiovascular outcomes more accurately and, to a large extent, to rule out the influence of secular trends or random changes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the cardiovascular sequelae of the COVID-19 pandemic mostly reported decreases in cardiovascular diagnoses and medical procedures in the initial phase of the pandemic [6][7][8][9][10]. Different trends were observed as the pandemic proceeded [11].…”
Section: Introductionmentioning
confidence: 99%